Genome-wide association study identifies HLA 8.1 ancestral haplotype alleles as major genetic risk factors for myositis phenotypes - Miller, F W; Chen, W; O'Hanlon, T P; Cooper, R G; Vencovsky, J; Rider, L G; Danko, K; Wedderburn, L R; Lundberg, I E; Pachman, L M; Reed, A M; Ytterberg, S R; et al. (Genes and immunity, 2015)
Autoimmune muscle diseases (myositis) comprise a group of complex phenotypes influenced by genetic and environmental factors. To identify genetic risk factors in patients of European ancestry, we conducted a genome-wide association study (GWAS) of the major myositis phenotypes in a total of 1710 cases, which included 705 adult dermatomyositis, 473 juvenile dermatomyositis, 532 polymyositis and 202 adult dermatomyositis, juvenile dermatomyositis or polymyositis patients with anti-histidyl-tRNA synthetase (anti-Jo-1) autoantibodies, and compared them with 4724 controls. Single-nucleotide polymorphisms showing strong associations (P<5×10(-8)) in GWAS were identified in the major histocompatibility complex (MHC) region for all myositis phenotypes together, as well as for the four clinical and autoantibody phenotypes studied separately. Imputation and regression analyses found that alleles comprising the human leukocyte antigen (HLA) 8.1 ancestral haplotype (AH8.1) defined essentially all the genetic risk in the phenotypes studied. Although the HLA DRB1*03:01 allele showed slightly stronger associations with adult and juvenile dermatomyositis, and HLA B*08:01 with polymyositis and anti-Jo-1 autoantibody-positive myositis, multiple alleles of AH8.1 were required for the full risk effects. Our findings establish that alleles of the AH8.1 comprise the primary genetic risk factors associated with the major myositis phenotypes in geographically diverse Caucasian populations.
Keywords: Autoantibodies; alely; celogenomová asociační studie; Polymorphism, Single Nucleotide; haplotypy; Humans; dermatomyozitida; Case-Control Studies; Myositis; genetické asociační studie; lidé středního věku; myozitida; běloši; studie případů a kontrol; jednonukleotidový polymorfismus; Female; rizikové faktory; dospělí; Haplotypes; Alleles; White People; lidé; Dermatomyositis; HLA antigeny; polymyozitida; Adult; Polymyositis; ženské pohlaví; Genetic Association Studies; Male; autoprotilátky; Middle Aged; Adolescent; genetická predispozice k nemoci; Genetic Predisposition to Disease; Genome-Wide Association Study; mužské pohlaví; HLA Antigens; mladiství; Risk Factors